ASSESSMENT OF ADEQUACY OF EQUIPMENT, MOTIVATION AND INCENTIVES OF THE NIGERIAN POLICE FORCE: IMPLICATIONS FOR EFFECTIVE POLICING IN NIGERIA - Onuoha, Ogobuchi Onuoha (EBSU Journal of Social Sciences and Humanities, 2024)
This paper is designed to assess the adequacy of equipment, motivation and incentives of the Nigerian police force and its implications for effective policing in Nigeria. Over time, successive governments have not paid maximum premium towards enhancing effective policing in Nigeria. Theoretical review approach was adopted to review different articles published by different authors using online platforms. Technological equipment were found to be pivotal in enhancing police effectiveness but such technological equipment were not seen to be adequate thereby limiting the effective operation of the police. Pay rise, good working environment, hygiene, recognition, rewards, promotion and some other indicators were identified as motivational and incentive drives that can boost the morale and productivity of the Police personnel but were not sufficient. It was concluded that the problem of Nigerian police is not with the personnel but as a result inadequate equipment and inappropriate motivation. It recommended that the police force should be provided with proper equipment and adequate incentives to bring out the best in the personnel.